2015
DOI: 10.1111/acer.12848
|View full text |Cite
|
Sign up to set email alerts
|

Active Ingredients of Treatment and Client Mechanisms of Change in Behavioral Treatments for Alcohol Use Disorders: Progress 10 Years Later

Abstract: Background The current review revisits the article entitled: Active Ingredients of Behavioral Treatments for Alcohol Use Disorders (AUDs) published in Alcoholism: Clinical and Experimental Research. This work summarized proceedings from a 2004 Symposium of the same name that was held at the Annual Meeting of the Research Society on Alcoholism (RSA). A decade has passed, which provides occasion for an evaluation of progress. In 2014, an RSA symposium titled Active Treatment Ingredients and Client Mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 90 publications
2
69
0
Order By: Relevance
“…There is evidence that personality can change through treatment (e.g., Zapolski and Smith, 2016); however, many SUD psychotherapies target factors that mediate the relationship between impulsive personality traits and substance use (e.g., coping motives, benefit perceptions, and self-efficacy; e.g., Kiluk et al, 2010; Witkiewitz et al, 2012; Magill et al, 2015) and few directly target impulsive personality traits (e.g., Zapolski and Smith, 2016). Changing mechanisms, but not the more distal factor of impulsive personality, leaves one at risk for poorer outcomes through a number of other mechanisms of impulsive personality’s influence on substance use.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that personality can change through treatment (e.g., Zapolski and Smith, 2016); however, many SUD psychotherapies target factors that mediate the relationship between impulsive personality traits and substance use (e.g., coping motives, benefit perceptions, and self-efficacy; e.g., Kiluk et al, 2010; Witkiewitz et al, 2012; Magill et al, 2015) and few directly target impulsive personality traits (e.g., Zapolski and Smith, 2016). Changing mechanisms, but not the more distal factor of impulsive personality, leaves one at risk for poorer outcomes through a number of other mechanisms of impulsive personality’s influence on substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Gains in S/R practices have been found to be predictive of reductions in drinking behavior (Robinson, Cranford, Webb, & Brower, 2007; Tonigan, 2007; Tonigan, Rynes, & McCrady, 2013; Zemore, 2007). Interestingly, using meta-analytic techniques (Tonigan, 2015; in Magill et al, 2015), Tonigan reported that the magnitude of the association between frequency of AA attendance and later gains in AA-prescribed S/R practices such as prayer and meditation was homogeneous in nine AA studies. It would appear, then, that the spiritually/religiously based prescriptions and messages of AA are both consistently expressed in AA meetings as well as adopted by early AA affiliates.…”
Section: Religiosity/spirituality As a Mechanism Of Changementioning
confidence: 99%
“…Approximately 9% of adults in the United States have attended AA, and almost 80% of adults who have sought help for alcohol-related problems have participated in AA (Dawson, Grant, Stinson, & Chou, 2006; Moos, 2008). The high rate of AA participation is partially attributable to the widespread availability of AA programs around the world, and more importantly, AA referral is grounded on the recommendations of five meta-analytic studies that have consistently reported positive associations between frequency of AA attendance and increased abstinence (Emrick, Tonigan, Montgomery, & Little, 1993; Forcehimes & Tonigan, 2008; Magill, Kiluk, McCrady, Tonigan, & Longabaugh, 2015; Tonigan, Toscova, & Miller, 1996). …”
mentioning
confidence: 99%
“…Mechanisms of change in CBT for AUD are an important research area (Magill, Kiluk, McCrady, Tonigan, & Longabaugh, 2015), and examining SGs may advance these efforts. For instance, in their study of SGs in CBT for women with AUD, Drapkin et al (2015) found that one-third of the sample experienced SGs in at least one drinking domain (alcohol use frequency, frequency of urges for alcohol, and/or intensity of alcohol urges) during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among some women, higher self-efficacy to deal with negative emotions (perhaps because they have other ways of coping with negative emotion) may attenuate the negative emotion-drinking relationship, as these women may have other ways of dealing with negative emotion. Enhancing general self-efficacy for alcohol abstinence is a well-established mechanism of action in CBT for AUD (Magill et al, 2015); however enhancing self-efficacy not to drink when stressed or in a negative emotional state by providing alternative skills for coping with negative emotion is not necessarily standard in AUD treatment protocols. Interventions directly focused on regulating emotions may be particularly beneficial for women who have high levels of depression and/or anxiety, as their goal is to reduce depression and anxiety, decreasing or eliminating a common trigger to drink.…”
Section: Introductionmentioning
confidence: 99%